Unusual Cause of Orocutaneous Fistula in the Neck - Sudipta Saha; Ashesh Jha; Navneet Kaur (Case Reports in Surgery)
A case of orocutaneous fistula secondary to submandibular sialolithiasis, which was masquerading clinically as branchial fistula is presented. This case highlights the importance of conducting fistulogram in the evaluation of discharging lesions in the neck.